Validating baseball bat compliance - Gamache, P.; Galante, A.; Seben, G.; Elbirt, a J. (Sports Engineering, 2007)
Professional baseball players have attempted to illegally modify baseball bats in the hopes of increasing bat speed and thus the distance travelled by batted balls. To date, no low-cost, noninvasive, real-time solution exists to this problem. Previously proposed solutions to this problem that involved using radar to measure the scatter signature of a scanned baseball bat were found to be extremely expensive. Ultrasound technology offers the ability to provide equivalent scatter signature measurements as compared to radar technology at a much lower cost and level of complexity while still operating in real time. We therefore present an ultrasound-based implementation of a prototype for a hand-held scanner unit designed to detect illegally modified baseball bats. A detailed discussion of the performance enhancements resulting from illegally modifying a baseball bat will be provided and an analysis of the attenuative properties of wood will be presented to determine appropriate sample rates for the ultrasound unit. Data acquisition issues encountered in prototyping the scanner will be examined and measurement data for both solid wood bats and modified bats will be evaluated to determine the effectiveness of the ultrasound-based data acquisition unit and the prototype’s ability to distinguish between both types of scatter signatures.
Keywords: baseball; bat; corked; scatter; signature; ultrasound